Clinical Significance of Medial Versus Lateral Compartment Patellofemoral Osteoarthritis: Cross‐Sectional Analyses in an Adult Population With Knee Pain. Issue 7 (July 2017) - Ukachukwu, Vincent; Duncan, Rachel; Belcher, John; Marshall, Michelle; Stefanik, Joshua; Crossley, Kay; Thomas, Martin J.; Peat, George
Abstract : Objective: To determine the comparative prevalence, associations with selected patient characteristics, and clinical outcomes of medial and lateral compartment patellofemoral (PF) joint osteoarthritis (OA). Methods: Information was collected by questionnaires, clinical assessment, and radiographs from 745 eligible community‐dwelling symptomatic adults age ≥50 years. PF joint space narrowing (JSN) and osteophytes were scored from skyline radiographs using the Osteoarthritis Research Society International atlas. Multilevel models were used to assess associations of compartmental PF joint OA with age, sex, body mass index (BMI) and varus–valgus malalignment, while median regression was used to examine associations with clinical outcomes (current pain intensity on a numeric rating scale [0–10] and the function subscale of the Western Ontario and McMaster Universities Osteoarthritis Index [0–68]). Results: Isolated lateral PF joint OA was more common than isolated medial PF joint OA, particularly at higher severity thresholds. Irrespective of severity threshold, age (≥2 odds ratio [OR] 1.19 [95% confidence interval (95% CI) 1.12, 1.26]), BMI (≥2 OR 1.15 [95% CI 1.07, 1.24]), and valgus malalignment (≥2 OR 2.58 [95% CI 1.09, 6.07]) were associated with increased odds of isolated lateral JSN, but isolated medial JSN was only associated with age (≥2 OR 1.20 [95% CI 1.14, 1.27]). The pattern of association was less clear for PF joint osteophytes. Isolated lateral PF joint OA, defined by JSN or osteophytes, was associated with higher pain scores than isolated medial PF joint OA, but these differences were modest and were not significant. A similar pattern of association was seen for functional limitation but only when PF joint OA was defined by JSN. Conclusion: Isolated lateral PF joint OA is more common than isolated medial PF joint OA, and it is more consistently associated with established OA risk factors. It is also associated with higher, but clinically nonsignificant, pain and function scores than isolated medial PF joint OA, particularly when PF joint OA is defined using JSN.